PROFILE OF STUDENTS’ COMPUTATIONAL THINKING BASED ON SELF-REGULATED LEARNING IN COMPLETING BEBRAS TASKS - Diah Nuraisa; Hairul Saleh; Sigit Raharjo (Prima: Jurnal Pendidikan Matematika, 2021)
Bebras task is a problem solving problem that integrates computational thinking in it, which the stages in computational thinking consist of: decomposition, abstraction, algorithm, and pattern recognition. This study aims to describe the profile of student’s computational thinking based on the level of self-regulated learning in completing bebras task. This study is a qualitative-descriptive study with three research subjects based on the level of students’ self-regulated learning, namely high self-regulated learning, medium self-regulated learning, and low self-regulated learning. The results of this study indicate that students with different levels of self-regulated learning have different computational thinking ability in completing bebras task. Student with high level of self-regulated learning can reach the stages of decomposition, abstraction, algorithm, and pattern recognition. Student with medium level of self-regulated learning can reach the stages of decomposition, absraction, and algorithm. Student with low level of self-regulated learning can reach the stage of decomposition only. Student with low level of self-regulated learning do not yet reflect independence in learning.